A theoretical view on concept mapping - Ray McAleese (Association for Learning Technology, 1994)
Auto-monitoring is the pivotal concept in understanding the operation of concept maps, which have been used to help learners make sense of their study and plan learning activities. Central to auto-monitoring is the idea of a 'learning arena' where individuals can manipulate concept representations and engage in the processes of checking, resolving and confirming understandings. The learner is assisted by familiar metaphors (for example, networks) and the possibility of thinking 'on action' while 'in action'. This paper discusses these concepts, and concludes by arguing that maps are part of the process of learning rather than a manifestation of learning itself. Auto-monitoring is suggested as an appropriate term to describe the process of engaging in the learning arena.